Peran Transformasi Digital dan Tantangan Inovasi Terhadap Keberlanjutan UMKM di Indonesia (Studi Literature Review) - Moh Hamzah; Ririn Filda Yanti Ningsih; Usasilah Faria Z.A; Milin Umroatul Ummah; Laily Fitriya (STKIP MAJENANG, 2023)
This research explores the challenges and opportunities faced by Micro, Small and Medium Enterprises (MSMEs) in implementing information technology (IT) and digitalization. Through a qualitative approach with in-depth interviews with MSME owners and managers in various sectors, the results show that MSMEs experience a number of obstacles such as limited financial resources, lack of technological knowledge, and inadequate infrastructure. However, the use of IT can increase efficiency, productivity and market access for MSMEs. External support such as technology training and subsidies from the government are important factors in overcoming this challenge. This research concludes that digital transformation is the key to increasing the competitiveness of MSMEs in the ever-growing digital era. It is hoped that the recommendations will help MSME owners and policy makers formulate strategies to support IT adoption effectively.